(untitled) (Bioscience Journal, 2017)
Wildlife road killing is a problem for animal conservation in the world. In order to mitigate this problem, it is necessary to understand the factors that affect it, like seasonality and climatic variables. The objective of the study was to evaluate the influence of climatic variables (mean temperature, relative air humidity and accumulated precipitation), seasonality and average daily traffic (ADT) on vertebrate roadkill rates in an area of Cerrado biome, Brazil. The study area is a stretch of 96 km of the highway BR-050, a four-lane road, between the cities of Uberlândia and Uberaba, state of Minas Gerais, Brazil. This area is characterized by intense fragmentation of natural areas, with few remnants of Cerrado biome. The climate has two very defined seasons, a warm and rainy summer and a very dry winter. We analyzed data from roadkill monitoring carried out from April 2012 to March 2013. The road was monitored weekly by car at an average speed of 60 km/h, by two observers, totaling 8,064 km surveyed. The highest roadkill rates for reptiles were recorded in the rainy season, for the other groups (mammals and birds) no difference was found. We also checked seasonality for the most abundant species: the highest number of roadkills was found in the rainy season for the common boa (Boa constrictor amarali) and for the six-banded armadillo (Euphractus sexcinctus). For the crab-eating fox (Cerdocyon thous), crab-eating raccoon (Procyon cancrivorus), striped hog-nosed skunk (Conepatus semistriatus) and red-legged seriema (Cariama cristata) we found no difference. The humidity and accumulated precipitation positively influenced the reptile roadkill rate. As expected, the same result was found for Boa constrictor amarali. Mammal roadkill rate increases with accumulated precipitation, on the other hand, Euphractus sexcinctus roadkill rate increases with temperature. Birds are not affected by climate variables, nevertheless, Cariama cristata roadkill rate decreases as humidity increases. Contrary to expectations, ADT had no influence on roadkill rates. These results show that it is necessary to investigate the influence of possible descriptor variables on mammals, birds and reptiles separately and not for all vertebrates as a group. Furthermore, certain species may even present different temporal patterns.